Chemistry of Protein-Phenolic Interactions Toward the Microbiota and Microbial Infections - Yilmaz, Hilal; Gultekin Subasi, Busra; Celebioglu, Hasan Ufuk; Ozdal, Tugba; Capanoglu, Esra (Frontiers in Nutrition, 2022)
Along with health concerns, interest in plants as food and bioactive phytochemical sources has been increased in the last few decades. Phytochemicals as secondary plant metabolites have been the subject of many studies in different fields. Breakthrough for research interest on this topic is re-juvenilized with rising relevance in this global pandemics’ era. The recent pandemics of COVID-19 get people attention to viral infections and molecular mechanisms behind these infections. Thus, the core of the present review is the interaction of plant phytochemicals with proteins as these interactions can affect the functions of co-existing proteins, especially focusing on microbial proteins. To the best of our knowledge, there is no work covering the protein-phenolic interactions based on their effects on microbiota and microbial infections. The present review collects and defines the recent data, representing the interactions of phenolic compounds -primarily flavonoids and phenolic acids- with various proteins and explores how these molecular-level interactions account for the human health directly and/or indirectly, such as increased antioxidant properties and antimicrobial capabilities. Furthermore, it provides an insight about the further biologic activities of interacted protein-phenolic structure from an antiviral activity perspective. The research on the protein-polyphenolic interaction mechanisms is of great value for guiding how to take advantage of synergistic effects of proteins and polyphenolics for future medical and nutritive approaches and related technologies.